Thực nghiệm và kiểm chứng tác động của một số biện pháp ứng dụng mô hình STEAM trong dạy học nội dung “Giáo dục địa phương” tại các trường trung học cơ sở ở một số tỉnh miền núi phía Bắc Việt Nam - Lê Thị Dung, Lê Thị Dung; Lường Hoài Thanh, Lường Hoài Thanh (Tạp chí Giáo dục, 2026)
In the context of educational reform toward competency-based learning, the application of integrated models such as STEAM in Local Education is increasingly necessary. This study evaluates the impact and effectiveness of pedagogicalmeasures applying STEAM in teaching Local Education at lower secondary schools in the northern mountainous region of Vietnam. The experiment was conducted in six schools across Lao Cai, Lang Son, and Dien Bien during the second semester of the 2024-2025 academic year, involving 12 teachers and 180 students, using a mixed-methods approach (pre- and postsurveys, t-test, correlation analysis, interviews, and classroom observations). The results show clear improvements in students’ problem-solving, collaboration, creativity, and local understanding, along with increased learning engagement. Teachers and school administrators highly valued the model’s feasibility, effectiveness, and potential for wider implementation. The study contributes to affirming the theoretical and practical value of applying STEAM in Local Education.